Simulation and experiment of carburized gear scuffing under oil jet lubrication. (September 2022) - Chen, Taimin; Zhu, Caichao; Liu, Huaiju; Wei, Peitang; Zhu, Jiazhan; Xu, Yongqiang
Highlights: An effective establishment of the gear temperature model is proposed. A wireless gear temperature measuring system is developed. Abstract: A systematic investigation on gear scuffing capacity under oil jet lubrication was presented numerically and experimentally. A sequence coupling numerical methodology was proposed for the effective establishment of the gear temperature model. A gear scuffing test under jet lubrication was designed and conducted, in which the gear temperature was measured via a developed wireless measuring system. The proposed testing method enables a quick evaluation of gear scuffing failure without frequently dismantling the gearbox. The simulated gear bulk temperature is compared with experimental results and shows consistency, the largest deviation between which during the whole gear scuffing test is 5.4%. The simulation model provides an efficient and reliable method for the evaluation of gear scuffing capacity.